Two new Geoplaninae species (Platyhelminthes: Continenticola) from Southern Brazil based on an integrative taxonomic approach - Rossi, Ilana; Amaral, Silvana Vargas; Ribeiro, Giovana Gamino; Cauduro, Guilherme Pinto; Fick, Israel; Valiati, Victor Hugo; Leal-Zanchet, Ana Maria (Journal of Natural HistoryJournal of Natural History, 2015)
The genera Cratera Carbayo et al., 2013 and Obama Carbayo et al., 2013, belonging to the subfamily Geoplaninae, were recently proposed to encompass some of the species that belonged to the genus Geoplana Stimpson, 1857. Herein we describe two new species of Geoplaninae, occurring in areas of ombrophilous forest which belong to the southern portion of the Brazilian Atlantic Rain Forest. The species are sympatric in their type-locality. In general, both new species herein described match the diagnostic characteristics of their genera. However, some of these features are noteworthy when characters of the new species are taken into consideration, especially the pattern of the sensory pits and the morphology of the prostatic vesicle. Both species are differentiated from their congeners by a combination of morphological characteristics, corroborated by phylogenetic analyses of the cytochrome c oxidase subunit I gene, using maximum likelihood and Bayesian inference, as well as the Automatic Barcode Gap tool.
doi: 10.1080/00222933.2015.1084057